Pengembangan Video Karungut Sebagai Media Pembelajaran PPKn pada Materi Norma dan Keadilan di Kelas VII SMP Muhammadiyah Palangka Raya - Musthafa, Ahmad Irfan; Offeny; Karliani, Eli (Sagita Academia Journal, 2024)
This study aims to develop a video-based learning media for Civics Education (PPKn) on the topic of norms and justice, using a karungut (traditional chant) approach. This research is a type of development research or Research and Development (R&D). The results of the research carried out are 1) The research steps include a) Definition, here what the researcher does is observe and look for problems faced by students in using PPKn learning media and determine how the video-based learning media will be used. b) Design, that is, the researcher designed a video-based learning media, guided by Core Competencies and Basic Competencies in the subject matter of norms and justice in Civics. c) Development, namely carrying out a feasibility test on the karungut video with material experts and media experts. 2) Validity aspect, assessment of the suitability of the material on the karungut video as a PPKn learning media on norms and justice material is based on validation sheets from material experts and media experts, where the three material expert lecturers and the three media expert lecturers have validated the karungut video as a PPKn learning media. on norms and justice material and is suitable for use with several changes according to suggestions or comments given and proven by the results of the analysis of assessment items.